1995
DOI: 10.1111/j.1460-2695.1995.tb00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shot Peening on Residual Stress and Fatigue Life of a Spring Steel

Abstract: This study describes shot peening effects such as shot hardness, shot size and shot projection pressure, on the residual stress distribution and fatigue life in reversed torsion of a 60SC7 spring steel. There appears to be a correlation between the fatigue strength and the area under the residual stress distribution curve. The biggest shot shows the best fatigue lie improvement. However, for a shorter time of shot peening, small hard shot showed the best performance. Moreover, the superficial residual stresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(85 citation statements)
references
References 8 publications
2
69
0
3
Order By: Relevance
“…Experimental results obtained by Farrahi et al [19] for a shotpeened cylindrical spring steel and by Smith et al [9] for shotblasted cylindrical steel bars will be used here to reconstruct the residual stress field. The residual stresses were measured in the hoop and axial directions with respect to the main axis of the bars.…”
Section: Article In Pressmentioning
confidence: 98%
“…Experimental results obtained by Farrahi et al [19] for a shotpeened cylindrical spring steel and by Smith et al [9] for shotblasted cylindrical steel bars will be used here to reconstruct the residual stress field. The residual stresses were measured in the hoop and axial directions with respect to the main axis of the bars.…”
Section: Article In Pressmentioning
confidence: 98%
“…The stability of the residual stress field has been investigated by a number of researchers for shot peened steel [13][14][15][16][17], nickel base superalloys [18][19][20], and titanium alloys [21]. However, the relaxation of LSP'd residual stress has not been extensively studied to date although resistance to fretting has been quantified [9].…”
Section: Introductionmentioning
confidence: 99%
“…[3] It is also well known that surface residual stresses introduced by a variety of surface treatment methods such as shot peening, fillet rolling, induction hardening, laser treatment, and simply machining can affect the fatigue performance of various metallic materials. [16][17][18][19][20][21][22][23][24][25][26] However, the effects of residual stress induced by surface treatment on the LCF behavior of Ni-base superalloys have been studied only rarely at elevated temperatures. Chang et al [27] reported that at room temperature, the fatigue life of M17 superalloys is increased by higher compressive residual stresses induced by creep-feed grinding.…”
Section: Introductionmentioning
confidence: 99%